Cytogenics, morphology and viability of Borreria spinosa (Rubiaceae) pollen grains (UNED Research Journal, 2024)
Introduction: Borreria spinosa is a herbaceous plant considered a weed in agricultural crops, although it also has potential in apiculture. Despite its agronomic importance, its cytogenetic and palynological traits are poorly known. Objective: To do the cytogenetic characterization of B. spinosa, describe the morphology of its pollen grains, and estimate their potential viability. Methods: We collected plant material in Santiago del Estero, Argentina, in May 2017 and used classical methods (8-hydroxyquinoline and Farmer for mitosis and meiosis; viability with Müntzing; pollen morphology with nonacetolysed and acetolysed techniques, and SEM). Results: B. spinosa has a chromosome number of 2n = 56, with a karyotype of 46 m + 10 sm. Meiotic abnormalities mainly include chromosomes outside the equatorial plate, lagging chromosomes, and cytomixis. Pollen grains are small to medium-sized, suboblate to oblate-spheroidal, with a viability of 70%. This is a tetraploid species, most chromosomes are metacentric or submetacentric; and it has irregular meiotic behavior and cytomixis, with concomitant low viability in pollen grains. Conclusion: In B. spinose, pollen grains have similar characteristics to other species of the genus Borreria.
Keywords: Cytomixis; karyotype; microsporogenesis; pollen morphology; weeds; palynology